Makerspaces in education: designing makerspace program to scaffold for conceptual understanding of young learners in STEM - Mohamed Nail, Lamiaa Mamdouh (AUC Knowledge Fountain, 2020)
The maker movement is impacting formal and non-formal education all over the world. Makerspaces are playing a critical role in supporting STEM education by providing opportunities for young learners to gather and share experiences, refine their understanding, and build creative artifacts. In Egypt, the formal education system is heavily focused on rote learning, where concepts are introduced in isolation and detachment from their real-world contexts. A design-based approach is proposed as an alternative, where makerspaces serve as stimulating environments that could potentially support concept learning in STEM. However, there is gab in our understanding of how learning STEM concepts can be scaffolded in a design-based learning experience in a makerspace environment. This research aimed towards exploring the dynamics of concept learning in a makerspace educational program for young learners, by adopting the design thinking process as a framework for structuring the learning experience. Methodologically, the study followed a design-based research (DBR) using a qualitative approach. The DBR process started with designing an educational program, followed with implementation, where data was collected through: audio and video recording, interviews, and observations, and finally thematic analysis took place to draw conclusions and come up with a set of design principles for educational programs in makerspaces with the aim of scaffolding concepts in STEM. Findings of this research sheds the light on the rich and complex interaction between problem solving and concept learning processes in a makerspace learning environment, with a noticeable impact of user-centered design, as well as, makerspace tools and objects on learning STEM concepts and ideas. The study also suggests potential improvements of educational program design so that it would better scaffold STEM concepts in makerspaces.